Efficient One-Pot Synthesis of Triazole-Linked Morpholinone Scaffolds by CuAAC in the Presence of 18-Crown-6 - Mayooufi, A.; Romdhani-Younes, M.; Thibonnet, J. (SynOpen, 2018)
A range of bis-heterocyclic derivatives based on novel morpholinone and triazole heterocycles was prepared from iodo-morpholinone. The key step in our strategy is a one-pot procedure based upon copper-catalysed alkyne-azide cycloaddition (CuAAC) from iodo-morpholinone.
Keywords: click chemistry; iodolactonization; morpholinones; azides; 1,2,3-triazole; one-pot procedure